Association of Clinically Diagnosed Anaemia with Walking in Barefoot among Children Studying at a Primary School in Rural Area of Bangladesh - Yusuf, Md Abdullah; Sultana, Sharmeen; Jahan, Tarana; Hassan, Mohammad Sayeed; Islam, Rafiqul; Uddin, Bhuiyan Mohammad Mahtab (Journal of Monno Medical College, 2025)
Background: Nutritional status is the main concern among the children both under five years of age and primary school going children. Anaemia and malnutrition are likely to be happened in those groups of children especially the primary school going children due to walking in barefoot. Objective: The aim of the present study was to evaluate the nutritional status of bare-footed children among primary schools’ level. Methodology: This comparative cross-sectional study was undertaken at the Umargong village of Kanaighat Upazila in Sylhet District from October 2010 to March 2011 for a period of 6 months. The children of primary school level at any age of both sexes were included in this study. Clinical examination of the students and anthropometric measurements were recorded accordingly. Anaemia was diagnosed clinically. A predesigned questionnaire was prepared for the collection of data from the children. Results: A total number of 60 primary school children were taken as case of which 44 were in the age group of less than 10 years with female predominance (76.7%). The height, weight, mid arm circumference and anaemia were examined and found a strong correlation with walking in barefoot and anaemia which is statistically significant (p=0.001). Conclusion: In conclusion, it may permit to conclude that walking in barefoot by the primary school children is the causes of anemia and malnutrition. Journal of Monno Medical College December, 2024;10 (2):89-93